Tingkat literasi keuangan syariah santri dayah - Khairatun Hisan; Farhatul Muhaya; Safwan Kamal (IAIN Langsa, 2021)
This study aims to determine the level of Islamic financial literacy of students at Dayah Raudhatul Huda. Aspects of Islamic financial literacy observed including knowledge of basic Islamic finance, Islamic saving and loans, personal finance, contracts in Islamic finance and understanding of Islamic financial institutions. The population in this study were the Senior High students of Dayah Raudhatul Huda with the sample size of 77. The data analysis method used is descriptive statistics. The results showed that the level of Islamic financial literacy of students at Dayah Raudhatul Huda was 68,10% which is categorized as medium.The average value obtained in the aspects of basic Islamic financial knowledge is 74,38%, Islamic savings and loans of 69,35%, personal finance of 54,97%, contract in Islamic finance of 69,34% and understanding of Islamic financial institutions at 72,50%.